Sulfone-containing covalent organic frameworks for photocatalytic hydrogen evolution from water - Wang, Xiaoyan; Chen, Linjiang; Chong, Samantha Y.; Little, Marc A.; Wu, Yongzhen; Zhu, Wei-Hong; Clowes, Rob; Yan, Yong; Zwijnenburg, Martijn A.; Sprick, Reiner Sebastian; Cooper, Andrew I. (Nature chemistry, 2018)
Nature uses organic molecules for light harvesting and photosynthesis, but most man-made water splitting catalysts are inorganic semiconductors. Organic photocatalysts, while attractive because of their synthetic tunability, tend to have low quantum efficiencies for water splitting. Here we present a crystalline covalent organic framework (COF) based on a benzo-bis(benzothiophene sulfone) moiety that shows a much higher activity for photochemical hydrogen evolution than its amorphous or semicrystalline counterparts. The COF is stable under long-term visible irradiation and shows steady photochemical hydrogen evolution with a sacrificial electron donor for at least 50 hours. We attribute the high quantum efficiency of fused-sulfone-COF to its crystallinity, its strong visible light absorption, and its wettable, hydrophilic 3.2 nm mesopores. These pores allow the framework to be dye-sensitized, leading to a further 61% enhancement in the hydrogen evolution rate up to 16.3 mmol g −1 h −1 . The COF also retained its photocatalytic activity when cast as a thin film onto a support. The inherent synthetic tuneability of organic materials makes them attractive in photocatalysis, but they tend to have low quantum efficiencies for water splitting. A crystalline covalent organic framework featuring a benzo-bis(benzothiophene sulfone) moiety has now been shown to exhibit high activity for photochemical hydrogen evolution from water.